Enterprise Knowledge-Based Generation of Class Model - Lopata, A.; Ambraziūnas, M.; Gudas, S.; Butleris, R.; Butkienė, R. (Elektronika ir Elektrotechnika, 2013)
The article presents Knowledge- Based MDA Class Model (UML notation) generation technique. Knowledge-Based MDA approach is a progressive Information Systems development method which combines the main components of traditional MDA and the best practices of Knowledge-Based Information Systems Engineering. The main advantage of such method is that problem domain knowledge acquainted at user requirements acquisition and business modelling stages are validated against formal criteria, in such way reducing empirical factors that could negatively impact the whole IS development process. The starting point of Class model generation process is a selection of particular entity from the Enterprise Model as the main class. System Analyst is able to select one of four elements types for class model generation process: Actor, Process, Information Activity and Flow. The main steps of Class model generation from Enterprise Model are presented in this article as well as Class model generation example. The final result of the generation process is the particular Class model that specifies static structure of the particular problem domain and can be used as business entities framework for developers of Information Systems. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.1717